From Insight to Innovation: Engineering Ideas That Transformed America in the Twentieth Century - Jr. (MIT Press, 2020)
Monograph
fulltext
Keywords: Communication, Networking and Broadcast Technologies; Components, Circuits, Devices and Systems; Computing and Processing; Engineering Profession; General Topics for Engineers